Exploration of phenylpropanoic acids as agonists of the free fatty acid receptor 4 (FFA4): Identification of an orally efficacious FFA4 agonist. Issue 5 (1st March 2017) - Sparks, Steven M.; Aquino, Christopher; Banker, Pierette; Collins, Jon L.; Cowan, David; Diaz, Caroline; Dock, Steven T.; Hertzog, Donald L.; Liang, Xi; Swiger, Erin D.; Yuen, Josephine; Chen, Grace; et al.
Graphical abstract: Abstract: The long chain free fatty acid receptor 4 (FFA4/GPR120) has recently been recognized as lipid sensor playing important roles in nutrient sensing and inflammation and thus holds potential as a therapeutic target for type 2 diabetes and metabolic syndrome. To explore the effects of stimulating this receptor in animal models of metabolic disease, we initiated work to identify agonists with appropriate pharmacokinetic properties to support progression into in vivo studies. Extensive SAR studies of a series of phenylpropanoic acids led to the identification of compound29, a FFA4 agonist which lowers plasma glucose in two preclinical models of type 2 diabetes.